Istrātījiyyāt al-Kalām al-Fa''ālah Ladā al-Muta'allimīn al-Nājiḥīn: Dirāsah bi-Ma'had Nūr al-Hidāyah bi-Riyāw, Indūnīsiyā Unmūdhajan - Nadwah Daud (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2016)
This study aims to identify the language learning strategies employed by successful learners in developing their Arabic speaking skills at Nūr al-Hidāyah Islamic Boarding School in Riau, Indonesia. The institution possesses distinctive characteristics that differentiate it from other Islamic boarding schools, particularly in its effective approach to teaching Arabic, with special emphasis on speaking proficiency. The participants were selected through purposive sampling and consisted of two male and two female students recognized as successful language learners at the institution. Data were collected through two research instruments: classroom observations and semi-structured interviews conducted during two language tasks, namely dramatic role-playing and oral presentations on assigned topics. The findings reveal that the participants employed both indirect and direct language learning strategies. Moreover, some participants effectively integrated listening and reading strategies to enhance their speaking performance.